Clinical characteristics and therapeutic outcomes of nosocomial super-infection in adult bacterial meningitis - Chang Chiung-Chih; Tsai Nai-Wen; Chuang Yao-Chung; Lu Cheng-Hsien; Chen Shu-Fang; Huang Chi-Ren; Wang Hung-Chen; Chien Chun-Chih; Chang Wen-Neng (BMC Infectious Diseases, 2011)
Abstract Background Super-infection in adult bacterial meningitis (ABM) is a condition wherein the cerebrospinal fluid (CSF) grows new pathogen(s) during the therapeutic course of meningitis. It is an uncommon but clinically important condition rarely examined in literature. Methods Twenty-seven episodes of super-infection states in 21 ABM patients collected in a 9.5-year study period (January 2001 to June 2010) were evaluated. The clinical characteristics, implicated pathogens, results of antimicrobial susceptibility tests, and therapeutic outcomes were analyzed. Results Twenty-one patients (13 men, 8 women) aged 25-73 years (median, 45 years) had post-neurosurgical state as the preceding event and nosocomial infection. The post-neurosurgical states included spontaneous intracranial hemorrhage (ICH) with craniectomy or craniotomy with extra-ventricular drainage (EVD) or ventriculo-peritoneal shunt (VPS) in 10 patients, traumatic ICH with craniectomy or craniotomy with EVD or VPS in 6 patients, hydrocephalus s/p VPS in 2 patients, and one patient each with cerebral infarct s/p craniectomy with EVD, meningeal metastasis s/p Omaya implant, and head injury. All 21 patients had EVD and/or VP shunt and/or Omaya implant during the whole course of ABM. Recurrent fever was the most common presentation and the implicated bacterial pathogens were protean, many of which were antibiotic resistant. Most patients required adjustment of antibiotics after the pathogens were identified but even with antimicrobial therapy, 33.3% (7/21) died. Morbidity was also high among survivors. Conclusions Super-infection in ABM is usually seen in patients with preceding neurosurgical event, especially insertion of an external drainage device. Repeat CSF culture is mandatory for diagnostic confirmation because most of the implicated bacterial strains are non-susceptible to common antibiotics used. Unusual pathogens like anaerobic bacteria and fungi may also appear. Despite antimicrobial therapy, prognosis remains poor.